Understanding domestic and international tourists' expenditure pattern in Melaka, Malaysia: result of CHAID analysis - Ab Rahman, Syakir Amir; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (Elsevier, 2015)
This study examined the tourists’ expenditure pattern in Melaka city. A total of 1500 diary record surveys were distributed, only 1000 surveys were collected. Chi-squared Automatic Interaction Detection (CHAID) was used to model interaction of domestic and international tourists in five tourism sectors-accommodation, food and beverages, transportation, entertainment and shopping. Results revealed that the tourists spent less on transportation (RM22.50 and below) and entertainment (RM22.50 and below), and heavily spent in other three sectors, shopping (RM475 and below), accommodation (RM700 and below), food and beverages(RM367 and below). The expenditure pattern modeling assists the relevant authorities in decision making.